1999
DOI: 10.2151/jmsj1965.77.3_721
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Inertia-Gravity Waves in the Lower Stratosphere Revealed by TOGA-COARE TOP Data

Abstract: Short-period disturbances in the equatorial lower stratosphere are analyzed by using radiosonde data of horizontal winds and temperature at 10 stations during the TOGA-COARE intensive observational period (IOP). The analysis is focused on disturbances whose periods are shorter than about 3 days.Time-height cross sections of both horizontal winds and temperature show the existence of disturbances with periods of about two days and vertical wavelengths of 3-5km. First, we made power and cross-spectral analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…Mesoscale convective complexes (MCC) also organize convection on much larger scales, however, and additionally excite considerable GW activity near inertial frequencies that may have significant influences to high altitudes (Pfister et al, 1986;Tsuda et al, 1994;Karoly et al, 1996;Shimizu and Tsuda, 1997;Garcia and Sassi, 1999;Wada et al, 1999;Vincent and Alexander, 2000).…”
Section: Convectionmentioning
confidence: 99%
“…Mesoscale convective complexes (MCC) also organize convection on much larger scales, however, and additionally excite considerable GW activity near inertial frequencies that may have significant influences to high altitudes (Pfister et al, 1986;Tsuda et al, 1994;Karoly et al, 1996;Shimizu and Tsuda, 1997;Garcia and Sassi, 1999;Wada et al, 1999;Vincent and Alexander, 2000).…”
Section: Convectionmentioning
confidence: 99%
“…Their meridional structure is more complex and their role in the large-scale tropical dynamics has been less evident, although some observational evidence has been provided (e.g. Wheeler and Kiladis 1999;Wada et al 1999;Clayson et al 2002) and theoretical scaling arguments furthermore confirm their physical relevance (Browning et al 2000). Figure 12(b) indicates that EIG waves exert an important influence on the tropical background-error correlations.…”
Section: (B) Sensitivity Experimentsmentioning
confidence: 99%
“…Intensive or periodic observations with fine vertical resolution have revealed characteristics of gravity waves in the tropical region (e.g., Tsuda et al 1994;Maruyama 1994;Sato et al 1994;Sato and Dunkerton 1997;Wada et al 1999). Radiosonde observations have revealed that momentum transported by short-period (#;3 days) gravity waves is comparable to that transported by long-period Kelvin waves (Maruyama 1994;Sato and Dunkerton 1997).…”
Section: Introductionmentioning
confidence: 99%